Use of platelet transfusions prior to lumbar punctures or epidural anaesthesia for the prevention of complications in people with thrombocytopenia - Estcourt, L; Malouf, R; Hopewell, S; Doree, C; Van Veen, J (John Wiley & Sons, Ltd, 2018)
Background People with a low platelet count (thrombocytopenia) often require lumbar punctures or an epidural anaesthetic. Lumbar punctures can be diagnostic (haematological malignancies, subarachnoid haematoma, meningitis) or therapeutic (spinal anaesthetic, administration of chemotherapy). Epidural catheters are placed for administration of epidural anaesthetic. Current practice in many countries is to correct thrombocytopenia with platelet transfusions prior to lumbar punctures and epidural anaesthesia, in order to mitigate the risk of serious procedure-related bleeding. However, the platelet count threshold recommended prior to these procedures varies significantly from country to country. This indicates significant uncertainty among clinicians regarding the correct management of these patients. The risk of bleeding appears to be low, but if bleeding occurs it can be very serious (spinal haematoma). Consequently, people may be exposed to the risks of a platelet transfusion without any obvious clinical benefit. This is an update of a Cochrane Review first published in 2016. Objectives To assess the effects of different platelet transfusion thresholds prior to a lumbar puncture or epidural anaesthesia in people with thrombocytopenia (low platelet count). Search methods We searched for randomised controlled trials (RCTs), non-randomised controlled trials (nRCTs), controlled before-after studies (CBAs), interrupted time series studies (ITSs), and cohort studies in CENTRAL (the Cochrane Library 2018, Issue 1), MEDLINE (from 1946), Embase (from 1974), the Transfusion Evidence Library (from 1950), and ongoing trial databases to 13 February 2018. Selection criteria We included RCTs, nRCTs, CBAs, ITSs, and cohort studies involving transfusions of platelet concentrates, prepared either from individual units of whole blood or by apheresis, and given to prevent bleeding in people of any age with thrombocytopenia requiring insertion of a lumbar puncture needle or epidural catheter. The original review only included RCTs. Data collection and analysis We used standard methodological procedures expected by Cochrane for including RCTs, nRCTs, CBAs, and ITSs. Two review authors independently assessed studies for eligibility and risk of bias and extracted data. Results were only expressed narratively. Main results We identified no completed or ongoing RCTs, nRCTs, CBAs, or ITSs. No studies included people undergoing an epidural procedure. No studies compared different platelet count thresholds prior to a procedure. In this update we identified three retrospective cohort studies that contained participants who did and did not receive platelet transfusions prior to lumbar puncture procedures. All three studies were carried out in people with cancer, most of whom had a haematological malignancy. Two studies were in children, and one was in adults. The number of participants receiving platelet transfusions prior to the lumbar puncture procedures was not reported in one study. We therefore only summarised in a narrative form the relevant outcomes from two studies (150 participants; 129 children and 21 adults), in which the number of participants who received the transfusion was given. We judged the overall risk of bias for all reported outcomes for both studies as 'serious' based on the ROBINS-I tool. No procedure-related major bleeding occurred in the two studies that reported this outcome (2 studies, 150 participants, no cases, very low-quality evidence). There was no evidence of a difference in the risk of minor bleeding (traumatic tap) in participants who received platelet transfusions before a lumbar puncture and those who did not receive a platelet transfusion before the procedure (2 studies, 150 participants, very low-quality evidence). One of the 14 adults who received a platelet transfusion experienced minor bleeding (traumatic tap; defined as at least 500 x 106/L red blood cells in the cerebrospinal fluid); none of the seven adults who did not receive a platelet transfusion experienced this event. Ten children experienced minor bleeding (traumatic taps; defined as at least 100 x 106/L red blood cells in the cerebrospinal fluid), six out of the 57 children who received a platelet transfusion and four out of the 72 children who did not receive a platelet transfusion. No serious adverse events occurred in the one study that reported this outcome (1 study, 21 participants, very low-quality evidence). We found no studies that evaluated all-cause mortality within 30 days from the lumbar puncture procedure, length of hospital stay, proportion of participants who received platelet transfusions, or quality of life. Authors' conclusions We found no evidence from RCTs or non-randomised studies on which to base an assessment of the correct platelet transfusion threshold prior to insertion of a lumbar puncture needle or epidural catheter. There are no ongoing registered RCTs assessing the effects of different platelet transfusion thresholds prior to the insertion of a lumbar puncture or epidural anaesthesia in people with thrombocytopenia. Any future study would need to be very large to detect a difference in the risk of bleeding. A study would need to be designed with at least 47,030 participants to be able to detect an increase in the number of people who had major procedure-related bleeding from 1 in 1000 to 2 in 1000. The use of a central data collection register or routinely collected electronic records (big data) is likely to be the only method to systematically gather data relevant to this population.